The Reality of Big Data in Libya and Its Readiness to Support Artificial Intelligence Applications - Ben Jred, Abdalslam (AlQalam Journal of Medical and Applied Sciences, 2025)
Big Data has emerged as a critical driver of Artificial Intelligence (AI) innovation, enabling intelligent decision-making, predictive analytics, and automation across sectors. However, the readiness of developing nations to integrate Big Data into AI ecosystems remains underexplored. This study examines Libya’s current Big Data landscape and its capacity to support AI applications. A mixed-methods approach was employed, combining desk research with semi-structured interviews involving eight stakeholders from government, academia, and the private sector. Findings reveal substantial deficiencies in infrastructure, data governance, policy frameworks, human capital, and institutional collaboration, which collectively hinder AI adoption. Benchmarking against advanced AI-ready nations such as Estonia and the United Arab Emirates (UAE) highlights Libya’s significant lag in key readiness indicators. The study contributes to the literature on AI readiness in post-conflict and developing contexts, offering an empirically grounded analysis that identifies priority areas for intervention. Strategic recommendations are proposed, including the development of a national AI and Big Data strategy, the enactment of data governance legislation, targeted investments in ICT infrastructure, educational reforms, and mechanisms for cross-sector collaboration. These actions are essential to enable Libya to harness the socio-economic potential of AI and bridge the readiness gap with global leaders in digital transformation.